Odpowiedź :
Odpowiedź:
A. [tex]\frac{1,2+\frac{2}{3} }{2+3,6} = \frac{\frac{12}{10}*\frac{3}{3} +\frac{2}{3} *\frac{10}{10} }{\frac{20}{10}+\frac{36}{10}}=\frac{\frac{36}{30} +\frac{20}{30}}{\frac{56}{10}}=\frac{\frac{56}{30}}{\frac{56}{10}}=\frac{56}{30} *\frac{10}{56} =\frac{10}{30} =\frac{1}{3}[/tex]
B. [tex]\frac{2,3-\frac{7}{5} }{\frac{3}{4} -1} = \frac{\frac{23}{10}-\frac{7}{5}*\frac{2}{2}}{\frac{3}{4} -\frac{4}{4}}= \frac{\frac{23}{10}-\frac{14}{10}}{-\frac{1}{4}}=\frac{\frac{9}{10}}{-\frac{1}{4}}=\frac{9}{10} *(-4 )=-\frac{18}{5}[/tex]
C.
[tex]2\frac{1}{2} -0,7*(1,2-\frac{3}{5} )=\frac{5}{2} -\frac{7}{10} *(\frac{12}{10} -\frac{3}{5} *\frac{2}{2} )=\frac{5}{2}*\frac{5}{5} -\frac{7}{10} *(\frac{12}{10} -\frac{6}{10})=\\=\frac{25}{10} -\frac{7}{10} *\frac{6}{10} =\frac{25}{10} -\frac{42}{100} =\frac{25*10}{10*10} -\frac{42}{100} =\frac{250-42}{100} =\frac{208}{100} =\frac{52}{25}[/tex]